The Fauna and Ecology of Rural Swallows: A Comprehensive Study - Shokirova Gavkharkhan Nazigulomovna; G‘aniyev Jaloldinmirzo Qahramon o‘g‘li (Scientific Trends, 2025)
This paper delves into the ecological dynamics of rural swallow populations, focusing on species such as the Barn Swallow (Hirundo rustica), Tree Swallow (Tachycineta bicolor), and Pacific Swallow (Hirundo tahitica). Swallows are integral to rural ecosystems, serving as natural pest controllers and indicators of environmental health. The study examines their distribution, nesting behaviors, foraging patterns, and the impacts of agricultural practices and human activities on their populations. Through a synthesis of global research and localized observations, the paper aims to provide insights into the factors influencing swallow ecology and to propose conservation strategies to mitigate the challenges they face.
Keywords: Barn Swallow, Rural Ecology,Nesting Habitats, Agricultural Practices, Conservation Strategies.